2022
DOI: 10.3390/ijerph191811489
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Five-Item World Health Organization Well-Being Index

Abstract: Purpose: Research on the psychological well-being of caregivers of children diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD) suggests that the well-being of parents and caregivers has been negatively affected by the COVID-19 pandemic. Although the psychological well-being of caregivers is a major concern, few validated well-being measures exist for caregivers of children diagnosed with ADHD. Therefore, a valid self-report scale is needed to assess well-being during the pandemic. The brief Five-It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
1
6
0
2
Order By: Relevance
“…Tâm lý hạnh phúc có thể được coi là tổng thể của những thỏa mãn làm cho cuộc sống đáng sống, tạo nên một cực đối lập với nỗi đau tâm lý khi có ý định tự sát [1]. Mặc dù nhận thức được tầm quan trọng của hạnh phúc của người bệnh thời gian đầy thử thách này, nhưng đa phần các nghiên cứu tập trung vào vấn đề sức khỏe tâm thần ở bệnh nhân mắc COVID mà dường như bỏ quên đánh giá tâm lý hạnh phúc.…”
Section: đặT Vấn đềunclassified
See 1 more Smart Citation
“…Tâm lý hạnh phúc có thể được coi là tổng thể của những thỏa mãn làm cho cuộc sống đáng sống, tạo nên một cực đối lập với nỗi đau tâm lý khi có ý định tự sát [1]. Mặc dù nhận thức được tầm quan trọng của hạnh phúc của người bệnh thời gian đầy thử thách này, nhưng đa phần các nghiên cứu tập trung vào vấn đề sức khỏe tâm thần ở bệnh nhân mắc COVID mà dường như bỏ quên đánh giá tâm lý hạnh phúc.…”
Section: đặT Vấn đềunclassified
“…Với tổng số 68 trẻ được chẩn đoán và phẫu thuật điều trị bệnh GĐQĐMC-TLT, tuổi trung vị lúc phẫu thuật là 23 ngày tuổi (khoảng tứ phân vị-IQR, 14 ngày -42,5 ngày), trẻ nam chiếm tỷ lệ 66,2%, cân nặng trung vị lúc phẫu thuật là 3,3 kg (IQR, 3 -3.6 kg). Có 57 bệnh nhân được phẫu thuật 1 thì bao gồm tạo hình quai ĐMC kèm theo vá lỗ TLT, 7 bệnh nhân 1 Trường Đại học Y Hà Nội 2 Bệnh viện Nhi Trung Ương Chịu trách nhiệm chính: Nguyễn Lý Thịnh Trường Email: nlttruong@gmail.com Ngày nhận bài: 26.12.2022 Ngày phản biện khoa học: 6.2.2023 Ngày duyệt bài: 27.2.2023 phẫu thuật tạm thời bắc cầu qua đường ra thất trái (ĐRTT) và 4 bệnh nhân được phẫu thuật sửa quai ĐMC kèm xiết bớt động mạch phổi. Thời gian theo dõi trung bình sau phẫu thuật của nhóm nghiên cứu là 35.5±29,5 tháng.…”
Section: Tóm Tắt3unclassified
“…The WHO-5 was originally derived from the WHO-10 (Bech et al, 1996), which, in turn, used valid items from Warr et al's (1985) research. Additionally, WHO-5 is widely used (Chan et al, 2022;Nyl en-Eriksen et al, 2022;Topp et al, 2015) and has been validated for different contexts such as Saudi Arabia (Kassab Alshayea, 2023). The WHO-5 contains five items, such as "I have felt cheerful and in good spirits."…”
Section: Subjective Employee Well-being (Sew)mentioning
confidence: 99%
“…WHO-5 Well-Being Index consisting of 5 items has been adapted into more than 30 languages, including Chinese [ 31 ], Persian [ 32 ], Sinhala [ 30 ], Norwegian [ 33 ], and Thai [ 34 ]. In previous studies examining the structure of the WHO-5 Well-being Index, it was similarly confirmed among Chinese university students that the 5-item scale was unidimensional, with reliability coefficients reported as 0.85 and 0.81 across two different datasets [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a different group, consisting of infertile patients, the unidimensional structure of the scale was also confirmed in the examined Persian version, and the Cronbach’s alpha coefficient was determined to be 0.86 [ 32 ]. When looking at the results for the Norwegian version, which was examined with caregivers, it was reported that the confirmatory factor analysis results showed a good fit, and the Cronbach’s alpha coefficient was similarly noted to be 0.86 [ 33 ]. In addition, the psychometric properties of the scale were evaluated during a cross-sectional study that spanned three countries—Spain, Chile, and Norway—to assess individuals’ well-being levels during the COVID-19 pandemic [ 35 ].…”
Section: Introductionmentioning
confidence: 99%